Błędy związane z wyrażaniem zgody na udzielenie świadczenia zdrowotnego - Lis, Wojciech (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The condition for providing a health service is the patient’s consent to it. The rules related to the consent to provide health service are legally regulated, in spite of this, they are still being violated. As a consequence, there is a breach of the guarantee of respect for the autonomy of the patient and his right to self-determination. These kind of activities of doctors do not find rational justification and may be brought to civil and criminal liability.